SEDIMENTASI FORMASI SEMILIR DI DESA SENDANG, WURYANTORO, WONOGIRI, JAWA TENGAH - Surono Surono (Pusat Survei Geologi, 2008)
Semilir Formation crops out widely along the Southern Mountains, the southern part of Central Jawa. This formation plays an important role in both stratigraphy and magmatism of the area. The formation is conformably underlain by turbidite-dominated sediments of Kebo Butak Formation and the upper part is overlain by the volcanic breccia of Nglanggran Formation.Â On the basis of lithological variation, the Semilir Formation can be distinguished into four units: sandstone, lapilli tuff, pumice breccia and andesitic pumice breccia. Â Calcareous clay within the sandstone unit contains nannofossils which indicate an Early Miocene age. On the other hand, fission track datings of zircon, which is contained in the pumice of the pumice breccia facies, have resulted in the ages of 17.0 + 0 Ma and 16.0 + 1.0 Ma or latest Early Miocene.The depositional environments of the formation indicate a shallowing upward sequence, and volcanism was very active during the deposition of the upper part of the formation. The pumice breccia and andesitic pumice breccia units were deposited in a relatively short time.Â Keywords: age, stratigraphy, lithologic unit, fission track